Sea urchins, sea stars and brittle stars from Terra Nova Bay (Ross Sea, Antarctica) - CHIANTORE, MARIACHIARA; ALBERTELLI, GIANCARLO; M. GUIDETTI; M. CAVALLERO; F. DE DOMENICO; CATTANEO VIETTI R. (Polar Biology, 2006)
Although echinoderms constitute some of the most conspicuous taxa of the Antarctic benthic communities, the echinoderm fauna of Terra Nova has not been described yet. The present study provides the first species list of echinoids, ophiuroids and asteroids from Terra Nova Bay (30–500 m depth) and describes the depth distribution of these species. Preliminary observations of the summer reproductive condition of some of the species are also included.